Epidemiology, pathophysiology and management of acute pancreatitis: A literature review (Research, Society and Development, 2024)
Introduction: Acute pancreatitis has an increasing incidence among all age groups. It’s typical presentation is marked by abdominal pain, vomiting and nausea and, among its causes, alcohol abuse and cholelithiasis are the most prominent. Although 80% of cases are mild manifestations, acute pancreatitis still has significant mortality and morbidity, therefore, this research aims to elucidate its aspects and understand the best management of the condition. Methodology: This is an integrative review on acute pancreatitis. Data from the Virtual Health Library (VHL), Scientific Electronic Library of Medicine (SciELO) and National Library of Medicine (PubMed) databases were used, by crossing the descriptors “acute pancreatitis”, “acute necrotizing pancreatitis”, “calculi biliary” and “alcohol abuse” to answer the question formulated through the PICO strategy. Results and Discussion: Acute pancreatitis affects approximately 34 out of every 100,000 people per year and risk factors include alcohol abuse, cholelithiasis, female gender, smoking, hypertriglyceridemia, among others. The diagnosis depends on 3 criteria, 2 of which are sufficient for this and clinical management depends on the severity of the presentation, with fluid therapy, cholecystectomy and ERCP being the highlights. The use of antibiotics as prophylaxis and drainage are still the subject of debate for the treatment of the disease. Conclusion: There is still a certain lack of knowledge about acute pancreatitis and some conflicts about its treatment and, therefore, more studies are needed to elucidate appropriate clinical management, the pathophysiology of the disease and how to eliminate risk factors.